Pengaruh Kemampuan, Motivasi Dan Pengembangan Karir Terhadap Kinerja Auditor Inspektorat Kabupaten Bengkalis - Wan Khairul Amri; Machasin '; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted at Inspectorate Bengkalis in order to determine how Influence Ability, Motivation, and Career Development simultaneously or partially on the Performance Auditor Bengkalis Inspectorate. The variables in this study are: Ability, Motivation and career development of the Performance Auditor Bengkalis Inspectorate. While the population in this study is Bengkalis Inspectorate Auditor, Auditor's Inspectorate Bengkalis totaling 29 people, and the whole Auditors sampled. Method of Multiple Linear Regression Analysis using SPSS version 21. Simultaneous regression (F test) showed that the independent variables studied (Ability, Motivation and Career Development) together (simultaneously) have a significant effect on the dependent variable (performance). The results of the testing that has been done, the partial regression test (t test) showed that each of the independent variables studied (Ability, Motivation and Career Development) has a significant effect on the dependent variable (performance). From the results of this research can be pursued to increase performance by increasing the ability, motivation, and apply the proper career development as one of the maintenance effort of human resources within the organizationKeywords: Performance, Ability, Motivation, and Career Development